1977
DOI: 10.1111/j.1432-1033.1977.tb11593.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Interrelationship of Prostaglandin Endoperoxide G2 and Cyclic Nucleotides in Platelet Function

Abstract: The prostaglandin endoperoxide Gz caused rapid aggregation and release of ADP and [14C]serotonin in human platelets. Since the presence of the ADP phosphorylating system creatine phosphate/ creatine phosphokinase markedly inhibited the aggregation caused by the endoperoxide, this effect seemed to be mediated mainly by ADP, which is instantaneously released by the endoperoxide.The prostaglandin G2 counteracted the increasing effect of prostaglandin El on the adenosine 3' : 5'-monophosphate (CAMP) levels in plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The other effects of oADP and oATP on the response to arachidonic acid ( Fig.6 and 7) appear consistent with the proposal that this response results both from a direct effect of thromboxane A2 and/or the endoperoxides on the platelet [8] as well as from a response to ADP secreted as a consequence of stimulation by these metabolites [36]. Thus the effect of oATP on the rate and extent of the aggregation response to a given arachidonate concentration (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…The other effects of oADP and oATP on the response to arachidonic acid ( Fig.6 and 7) appear consistent with the proposal that this response results both from a direct effect of thromboxane A2 and/or the endoperoxides on the platelet [8] as well as from a response to ADP secreted as a consequence of stimulation by these metabolites [36]. Thus the effect of oATP on the rate and extent of the aggregation response to a given arachidonate concentration (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…The role of ADP in thromboxane A 2 -induced platelet aggregation has been investigated using enzymes that deplete released ADP. This work suggested that the aggregation response is mediated by the secretion of platelet ADP (45)(46)(47)(48)(49). It was concluded that U46619-induced platelet aggregation depends on the release of stored ADP.…”
Section: Discussionmentioning
confidence: 97%
“…These experiments suggested that contact between platelet membranes was required for activation of guanylate cyclase and that increases in platelet cyclic GMP were more likely to be an effect than a cause of aggregation. Although one group has reported that exogenous cyclic GMP and derivatives can potentiate the platelet release reaction (Chiang et al 1976), others have not been able to reproduce this effect (Claesson andMalmsten 1977, Haslam 1978). In view of these considerations, it is conceivable that cyclic GMP is a feedback inhibitor of platelet responses rather than a mediator of platelet activation.…”
Section: Cyclic Gmpmentioning
confidence: 99%